SMART NETWORK REFERENCE DICTIONARY DEVELOPMENT USING WATERFALL FRAMEWORK MODEL TO IMPROVE LEARNING OUTCOMES - Purba, Ramen Antonov (Information Technology Education Department, 2026)
The purpose of this study is to develop a Smart Network Reference Dictionary using the Waterfall Framework Model to improve student learning outcomes. Information technology plays an essential role in enhancing student competence and expertise, especially in the Industrial Era 4.0, which demands skills aligned with the needs of industry and the business sector. Computer Networking is one of the subjects that requires strong mastery. Based on observations and interviews with lecturers at STMIK Methodist, out of 28 students, only seven passed with excellent categories, 11 with good categories, and ten did not pass, indicating the need for more effective learning support tools. This study developed the Smart Network Reference Dictionary using the SDLC approach with the Waterfall model and conducted validation through Black Box Testing and Alpha Testing, with Likert-scale analysis used to classify the results. The developed application achieved the Very Appropriate category, with assessment scores of 85.3%, 82.8%, and 86.0%, all of which fall under the Very Eligible classification. Furthermore, the learning outcomes of the experimental class improved significantly, as shown by the higher average pretest–posttest score range compared with the control class. Thus, the development of the Smart Network Reference Dictionary using the Waterfall Framework Model not only produces a high-quality application but also effectively enhances student learning outcomes in the Computer Networking course at STMIK Methodist.